Circadian variation of zinc, copper, selenium, and bromine in human milk - Mohd Taufek, Nor Hidayah; Hafiz Majdi, Hana' Nahlaa; Azhar, Aina Zafirah; Fata Nahas, Abdul Rahman; Mohmad Sabere, Awis Sukarni; Bidai, Joseph (IIUM Press, 2025)
Introduction: Human milk undergoes dynamic modifications throughout lactation to optimally meet the dietary and immunological requirements of the growing infant, with variations of its composition also occurring throughout the day. Circadian variation in some bioactive components helps the development of the biological clock by passing on chronobiological information from mother to infant. This study aimed to identify the circadian variation of zinc, copper, selenium, and bromine in human milk during the postpartum period. Methods: Human milk samples were collected from a postpartum mother who was taking zinc and copper supplements. Milk samples were analysed using inductively coupled plasma mass spectrometry. Data on zinc, copper, selenium, and bromine concentrations were analysed using Microsoft Excel 2021 and reported descriptively to determine circadian variation. Results: The concentration of all four trace elements declined throughout the six months postpartum period with consistent fluctuations for bromine. Zinc, copper, and bromine possess the most similar circadian variation throughout the day with a ‘V’ shaped pattern, but selenium showed inconsistent circadian pattern over the first six months postpartum. The ‘V’ shaped pattern generally disappeared in the fourth, fifth, and sixth months. Conclusion: Circadian rhythms for zinc, copper, selenium, and bromine varied during the first six months postpartum. This may indicate a functional circadian clock regulating infants’ biological development. Future studies should explore the factors influencing the development of fully functional circadian rhythmicity in infants.